Measuring Reliable Internet Connectivity Among Families with Children: Secondary Analysis of a US National Survey - Tran T Doan; Kelsey A Schweiberger; Samuel R Wittman; Tamar Krishnamurti; Sarah K Burns; Janel Hanmer; Kristin N Ray (Journal of Medical Internet Research)
Abstract BackgroundReliable internet connectivity is crucial for family participation in pediatric digital health care, including telehealth. Lack of internet connectivity is a barrier to pediatric telehealth access. While surveys commonly inquire about metrics, such as internet plan or device ownership, fewer measures exist for the reliability of internet connectivity when needed. There is limited knowledge of the national prevalence of reliable internet connectivity among households with children and how reports of reliable internet connectivity are associated with use of internet plans and devices. ObjectiveWe examined the prevalence of reliable internet connectivity among households with children and its association with digital technology access and sociodemographic factors. MethodsWe performed a secondary data analysis of a US national cross-sectional survey examining parents’ health-seeking decisions for children younger than 18 years old. The respondent panel was hosted by the National Opinion Research Center (NORC) AmeriSpeak. This analysis focused on survey items on reliable internet connectivity, digital technology access (internet plan type and device ownership type), and sociodemographic characteristics (education, employment, geographic region, race and ethnicity, and disability) of parent respondents and their children. The dependent variable was a binary indicator of household reliable internet connectivity. Respondents were categorized as having unreliable internet connectivity if they self-reported internet worry or unreliable internet experience. Unadjusted Rao-Scott ResultsThe final survey sample (N=1158) comprised 753 (55%) females, 614 (57%) non-Hispanic White, and 948 (81%) metropolitan respondents. There were 125 (12%) parents who reported internet worry, 152 (13%) parents who reported unreliable internet experience, and 76 (7%) parents who reported both. Combining these measures, we identified 201 (19%) parents with unreliable internet connectivity, defined as reporting either internet worry or unreliable internet experience. In contrast, 957 (81%) parents reported reliable internet connectivity in the household. In adjusted analysis, reliable internet connectivity was significantly associated with owning both nonmobile and mobile internet plans combined (86% reliable internet connectivity) versus nonmobile internet plan-only (67%; PPPPP ConclusionsOne-fifth of families with children experienced unreliable internet connectivity, highlighting an important dimension of the digital health divide that appears distinct from internet plan use or device ownership alone. Future research is needed to derive consensus on measuring reliable internet connectivity as a separate metric, including specifying the definition, survey questions, response options, and time frame of unreliability experience. Since reliable internet connectivity is needed for the growing field of digital health care, it is a critical issue for equitable pediatric health care access and delivery.